2017
DOI: 10.1074/jbc.m116.771253
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of ganglioside GM3 molecular species and a potential regulatory role during myoblast differentiation

Abstract: Edited by Gerald W. Hart Gangliosides (sialic acid-containing glycosphingolipids) help regulate many important biological processes, including cell proliferation, signal transduction, and differentiation, via formation of functional microdomains in plasma membranes. The structural diversity of gangliosides arises from both the ceramide moiety and glycan portion. Recently, differing molecular species of a given ganglioside are suggested to have distinct biological properties and regulate specific and distinct b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…reported that the serum GM3(d18:1-20:0) level was significantly elevated in subjects with visceral fat accumulation accompanied with hyperglycemia and dyslipidemia among the GM3 molecular species we have measured in the present study, while GM3(d18:1-16:0) and GM3(d18:1-24:1) levels were not altered 13 . A basic study also demonstrated the possible physiological importance of GM3 molecular species; the GM3(d18:1-16:0) content increased and the GM3(d18:1-24:1) content decreased during differentiation of mouse C2C12 myoblast cells 21 . Further studies are needed to elucidate the specific roles of GM3 molecular species.…”
Section: Discussionmentioning
confidence: 90%
“…reported that the serum GM3(d18:1-20:0) level was significantly elevated in subjects with visceral fat accumulation accompanied with hyperglycemia and dyslipidemia among the GM3 molecular species we have measured in the present study, while GM3(d18:1-16:0) and GM3(d18:1-24:1) levels were not altered 13 . A basic study also demonstrated the possible physiological importance of GM3 molecular species; the GM3(d18:1-16:0) content increased and the GM3(d18:1-24:1) content decreased during differentiation of mouse C2C12 myoblast cells 21 . Further studies are needed to elucidate the specific roles of GM3 molecular species.…”
Section: Discussionmentioning
confidence: 90%
“…Ganglioside GM3, produced by addition of sialic acid to LacCer ( Figure 1A ), is expressed mainly in adipose tissue and muscle in humans and mice, and liver and serum in humans ( Senn et al, 1989 ; Wentworth et al, 2016 ; Go et al, 2017 ; Inokuchi et al, 2018 ). GM3 expression in adipocytes is induced by stimulation of the inflammatory cytokines TNF-α and IL-1β, derived from tissue macrophages ( Tagami et al, 2002 ; Nagafuku et al, 2015 ).…”
Section: Regulatory Mechanisms Of Innate Immune Responses Mediated By...mentioning
confidence: 99%
“…Presently, BACE2 was most highly correlated with LV 2 (MetaMEx Aerobic Training, see Figure 2 for other pathway associations). The role of GM2A in skeletal muscle is poorly understood; however, it is typically involved in cholesterol and ganglioside processing (36), and recent work has linked gangliosides to developmental processes in C2C12 myoblasts (10). PLIER clustered GM2A with Type I myofiber markers in LV 6.…”
Section: Validationmentioning
confidence: 99%